The use of plethysmography and oscillometry to compare long-acting bronchodilators in patients with COPD - Borrill, Zoë L (Blackwell Science Inc, 2008)
AIMS: Assessment of bronchodilator pharmacology in chronic obstructive pulmonary disease (COPD) may be improved by using more sensitive methods than spirometry, such as impulse oscillometry (IOS) and body plethysmography. We sought to compare salmeterol (S) and tiotropium (Tio) using these methods. METHODS: In this double-blind, randomized, four-way crossover study, 32 COPD patients received single doses of Tio (18 µg), S (50 and 100 µg) or placebo. Specific airway conductance (sGaw), forced expiratory volume in 1 s (FEV(1)) and IOS were measured pre- and up to 26 h postdose. Comparisons between treatments were analysed by weighted means (WM) between 0 and 12 (WM 0–12 h) and 12–24 h (WM 12–24 h) postdose. Data are expressed as mean difference (or geometric ratio for nonparametric data) with 95% confidence intervals. RESULTS: Tio and S100 significantly improved FEV(1), sGaw and IOS parameters up to 26 h and S50 up to 16 h. WM analysis showed no difference between Tio and S100 in FEV(1) for 0–12 h or 12–24 h. Maximum mid-expiratory flow (−0.06; −0.11, −0.01) and R35 (0.02; 0.01, 0.03) demonstrated superiority of S100 compared with Tio for WM 0–12 h sGaw (1.12; 1.02, 1.23), R5 (−0.06; −0.09, −0.02), R15 (−0.03; −0.05, −0.01), and resonant frequency (RF) (−2.30; −3.83, −0.77) showed superiority of Tio compared with S100 for WM 12–24 h. At 26 h, sGaw, R5, R15, X5 and RF also showed superiority of Tio compared with S100. CONCLUSIONS: sGaw and IOS parameters sensitively differentiated between the effects of Tio and S when FEV(1) measurements were similar. Clinical trials in patients with COPD should use IOS and sGaw to assess comprehensively bronchodilator pharmacology.